CAUSES OF CONFLICT IN HABIBURRAHMAN EL-SHIRAZY’S NOVEL BUMI CINTA - Hamzah Sya’bani Nasution; M. Manugeren; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2020)
This study is concerned with the causes of conflicts in Habiburrahman El Shirazy’s Novel Bumi Cinta which was published in 2019. The causes of conflicts derived from internal and external factors are the focus of the study. Through this study it is found that Ayyas can protect himself from the temptation that attacks his faith. He also surrenders himself to God so that he could be saved from all disturbances that come at any time to him. He is very angry with Linor who regards that his religion is a primitive one. The method used to analyze the causes of the conflict in this study is literary descriptive approach proposed in which it is shown that qualitative research methods are complex, changing and contested field site of multiple methodologies and research practices. The research results show that the main character faces internal as well as external conflicts in the forms of temptation and difference in perception.